Effects of bariatric surgery on testosterone level and sexual function in men with obesity: A retrospective study - Guoji Chen; Guoji Chen; Guoji Chen; Guoji Chen; Luping Sun; Shuwen Jiang; Shuwen Jiang; Shuwen Jiang; Xiaomei Chen; Xiaomei Chen; Jie Zhu; Jie Zhu; et al. (Frontiers in Endocrinology, 2023)
IntroductionBariatric surgeries induce well-documented weight loss and resolve obesity comorbidities. Sexual function is one of the aspects of life quality and may benefit from surgery. Few studies have revealed the impact of bariatric surgeries on sexual function in Chinese men with obesity.MethodsThis is a retrospective cohort study of patients undergoing bariatric surgery [laparoscopic sleeve gastrectomy (LSG) or laparoscopic Roux-en-Y gastric bypass (LRYGB)]. Data were collected between September 2017 and February 2022. The International Index of Erectile Function (IIEF) questionnaire was used to evaluate erectile function, intercourse satisfaction, orgasmic function, sexual desire, and overall satisfaction. Sex hormones and other blood tests were evaluated before and at least 1 year after the surgery.ResultsFifty-nine Chinese male patients completed the IIEF questionnaire. The multivariate logistic regression analysis revealed that body mass index (BMI) was the single independent risk factor of the severity of erectile dysfunction (ED). Preoperative testosterone levels had negative correlations with BMI and waist circumference. Thirty-seven patients completed the postoperative questionnaire with a mean follow-up of 23.2 months.ConclusionBMI and waist circumference were negatively correlated with testosterone levels. BMI was an independent risk factor for the severity of ED. LSG and LRYGB led to positive and sustained improvement in sexual function of men with obesity. The two procedures had a comparable effect, more subjects being needed. Sex hormone levels also could be reversible. However, more weight loss did not predict a positive change in sexual function. A greater BMI loss might predict a greater increase in testosterone.